(3GdEJMGa aj fSH GdCTQGas - (3YeQ CZG GdMfajs
(3ChdgG (B:s
(3HSe Gddg (B... (3SCdfj HYV GdaVdGA ef CUMGHfG GdfHdGA Cf (B.. (3hCSdc Hg GhVM GdeSGdc aCLHJ dSDGdg QGLjG ef Gddg LRjd fhGdg eHfjG dG jOd ef Gdefbhd aj cJH GdaQhY hGdGUhds
(3BNQgG (B:s
.. (3aGQSdJ dg ecJhHG HGdJYXje hGdSdGe ajg HYV fbhd (B... (3Cf jWdYfj Ydi fbhd RGFOI (B...(3hgPG iNQ eG GfJXes
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3GdJedcGJ h GdhbajGJ (B:s
(3Jedc (B: (3eMeO CHh GdSYhO GdMSjfj , SfI (B1282 (3g`s
Keywords: (3GdJGQjNs